Measuring the strategic value of the Armed Forces Health Longitudinal Technology Application (AHLTA) - Bigelow, James H.; Harris, Katherine M.; Hillestad, R. J. (Richard John), 1942-; Rand eBooks (Santa Monica, CA : RAND, 2008)
The Military Health System (MHS) provides health care to active duty service members and their families, retirees and their families, and Guard and Reserve members serving on active duty and their families. In January 2004, the MHS began implementation of the Armed Forces Health Longitudinal Technology Application (AHLTA), DoD's global electronic health record system. AHLTA will ultimately be used by all providers in the military's direct care system at the point of care. The authors describe a four-part framework they recommend that DoD adopt in measuring AHLTA's contribution to MHS performance: (1) outcome measures capturing valued domains of system performance plausibly influenced by the presence of AHLTA; (2) "treatments"-ways of using AHLTA that are expected to influence one or more outcome measures, (3) a logic model describing the mechanisms or processes by which uses of AHLTA (i.e., treatments) influence outcome measures, and (4) an evaluation design for estimating AHLTA's effect on outcome measures in quantitative terms.
Introduction -- MHS Senior Leaders' Views on the Value of AHLTA -- Analyzing the Effect of AHLTA on the Strategic Performance of the Military Health System -- Potential Benefits of EMR Systems -- Measures for the MHS Strategic Objectives -- Strategic Management -- Concluding Comments -- Appendix: Catalog of NQMC Measures.
"A joint endeavor of RAND Health and the RAND National Defense Research Institute."
"RAND Center for Military Health Policy Research."
Includes bibliographical references (p. 95-99).
Also available on the internet via WWW in PDF format.
Keywords: Information storage and retrieval systems -- Medical care; Medical informatics -- United States; Medicine, Military -- United States -- Information services; Electronic books